Systematic review of HIV transmission between heterosexual serodiscordant couples where the HIV-positive partner is fully suppressed on antiretroviral therapy. - Mona R Loutfy; Wei Wu; Michelle Letchumanan; Lise Bondy; Tony Antoniou; Shari Margolese; Yimeng Zhang; Sergio Rueda; Frank McGee; Ryan Peck; Louise Binder; Patricia Allard; et al. (PLoS ONE)
Background The risk of sexual HIV transmission in serodiscordant couples when the HIV-positive partner has full virologic suppression on combination antiretroviral therapy (cART) is debated. This study aims to systematically review observational studies and randomized controlled trials (RCTs), evaluating rates of sexual HIV transmission between heterosexual serodiscordant couples when the HIV-positive partner has full suppression on cART. Methods and findings We searched major bibliographic databases to November 2012 for relevant observational studies and RCTs without language restrictions. Conference proceedings, key journals and bibliographies were also searched. Studies reporting HIV transmission rates, cART histories and viral loads of the HIV-positive partners were included. Two reviewers extracted methodologic characteristics and outcomes. Of 20,252 citations, 3 studies met all eligibility criteria with confirmed full virologic suppression in the HIV-positive partner. We included 3 additional studies (2 cohort studies, 1 RCT) that did not confirm viral suppression in the HIV-positive partner at transmission in a secondary meta-analysis. Methodologic quality was reasonable. The rate of transmission in the 3 studies confirming virologic suppression was 0 per 100 person-years (95% CI = 0-0.05), with low heterogeneity (I(2) = 0%). When we included the 3 studies that did not confirm virologic suppression, the rate of transmission was 0.14 per 100 person-years (95%CI = 0.04-0.31) (I(2) = 0%). In a sensitivity analysis including all 6 studies, the rate of transmission was 0 per 100 person-years (95%CI = 0-0.01) after omitting all transmissions with known detectable or unconfirmed viral loads, as full suppression in these cases was unlikely. Limitations included lack of data on same-sex couples, type of sexual intercourse (vaginal vs. anal), direction of HIV transmission, exact viral load at the time of transmission, sexually transmitted infections (STI) rates, and extent of condom use. Conclusions Our findings suggest minimal risk of sexual HIV transmission for heterosexual serodiscordant couples when the HIV-positive partner has full viral suppression on cART with caveats regarding information on sexual intercourse type, STIs, and condom use. These findings have implications when counseling heterosexual serodiscordant couples on sexual and reproductive health. More research is needed to explore HIV transmission risk between same-sex couples.